APPLICATION OF ORGANIC MANURE ON SWEETPOTATO (Ipomoea batatas (l.) Lam.) - Margo Yuwono; Nur Basuki; Lily Agustina (The Indonesian Green Technology Journal, 2012)
Objectives of this experiment are to (1) compare the growth and yield of sweet potato with organic matters treatment and with an inorganic treatment, (2) find out which type and proportion of organic matters is better for sweet potato growth and yield, (3) determining  starch and anthocyanin contents in tuber, and (4) determining N-residue after organic matter treatment. The experiment were conducted in the Field Experiment Station, Jatikerto village, Malang .    The field experiment  was arranged in Randomized Block Design and replicates three times. The treatments were kind of organic matters e.i. (1) cow manure (P1); (2) Calopogonium muconoides (P2); (3) Centrosema pubescens (P3 ) and (4) Tithonia diversifolia (P4) and dosage e.i. (1) equivalent  40 kg N/ha (D1), (2) equivalent 80 kg N/ha (D2), (3) equivalent 120 kg N/ha (D3) and  (4) equivalent 160 kg N/ha (D4) and inorganic fertilizer  were applied 80 kg N/ha. The organic matter with 80 kg N/ha proportion resulted better growth and yield  compare to in-organic fertilizer with the same proportion.  Refer to the sweet potato growth and yield as resulted of organic fertilizer treatment, T. diversifolia gave the best result.  The order among these organic manure was T. diversifolia > cow manure > C. muconoides > C. pubescens. The highest yield of fresh tuber obtained at T. diversifolia treatment that is 26.02 t/ha. The lowest yield of fresh tuber obtained at C. pubescens tratment that is 22.12 t/ha.  Combination between T. diversifolia with dosage 160 kg N/ha (equivalent 5.04 t/ha)) will give highest of fresh tuber (29.39 t/ha) and combination betweeen C. pubescens and dosage 40 kg N/ha (equivalent 1.36 t/ha) will give lowest of fresh tuber. The highest of strach content obtained at T. diversifolia treatment (31.78%) and the lowest obtained at  C. pubescens treatment (25.07%). The highest of anthocyanin content obtained at C. pubescens (2.69 mg/kg) and the inorganic treatment resulting the lowest amount of anthocyanin (0.99 mg/kg). The result indicated the amount of N-reidue at the end of the experiment is 21.08 kg/ha. Keyword : sweeet potato, organic manure, inorganic fertilizer